Village-level spatial differentiation and influencing factors of rural population hollowing in the agricultural areas of central China: a case study of Lankao County, Henan - Cheng, Lisha; Li, Xiaoyue; Ma, Li; Qiao, Jiajun (Frontiers in Sustainable Food Systems, 2025)
Rural hollowing is a manifestation of rural decline under rapid urbanization and industrialization, with population hollowing at its core. While most existing studies have been conducted at the county level, the relatively few village-level studies have mainly focused on Western and Northeastern China. In contrast, the densely populated villages of Central China, which are characterized by limited per capita cultivated land, have received comparatively less scholarly attention. Focusing on Lankao County—a representative agricultural region in Central China—this study integrates village-level geospatial and socio-economic data to investigate the spatial differentiation and influencing factors of rural population hollowing, employing spatial analysis and geodetectors. The findings show that: (1) Villages in Lankao County had a generally high population hollowing index (PHI), with a spatial distribution pattern characterized by higher values in the southwest and lower ones in the northeast. (2) The population hollowing levels of villages in Lankao County showed a significant positive spatial autocorrelation at the global level. The local spatial autocorrelation analysis revealed that significant villages predominantly exhibited LL and HH clusters. (3) Some factors have a certain explanatory power for the formation of the spatial distribution pattern of population hollowing in Lankao County in each of the following four dimensions: resource endowment, economic base, social welfare, and geographic location. Moreover, when any two factors interact, their explanatory power for the spatial distribution of population hollowing is enhanced. (4) Resource endowment, economic base, and social welfare determine the complementarity between villages and the outside world, while geographic location affects the accessibility between them. This study not only addresses the limitations of existing village-level research on rural population hollowing but also enriches the diversity of study areas, offering valuable insights for mitigating rural population outflow and promoting sustainable development in similar agricultural regions.